2023
DOI: 10.1038/s41467-023-43698-x
|View full text |Cite
|
Sign up to set email alerts
|

Green electrosynthesis of 3,3’-diamino-4,4’-azofurazan energetic materials coupled with energy-efficient hydrogen production over Pt-based catalysts

Jiachen Li,
Yuqiang Ma,
Cong Zhang
et al.

Abstract: The broad employment of clean hydrogen through water electrolysis is restricted by large voltage requirement and energy consumption because of the sluggish anodic oxygen evolution reaction. Here we demonstrate a novel alternative oxidation reaction of green electrosynthesis of valuable 3,3’-diamino-4,4’-azofurazan energetic materials and coupled with hydrogen production. Such a strategy could greatly decrease the hazard from the traditional synthetic condition of 3,3’-diamino-4,4’-azofurazan and achieve low-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…Based on experimental data and theoretical simulations, it was shown that the selectivity of the product can be tuned by controlling the proton–electron transfer reaction network. Recently, our group and co-workers 232 reported a novel oxidative reaction for the green electro-synthesis of DAAzF while simultaneously promoting hydrogen production. This emerging green electro-synthesis process can significantly reduce the environmental hazards caused by traditional industrial methods used to synthesize the DAAzF, and the assembled electrolyzer required only a low cell voltage of 1.55 V to reach 100 mA cm −2 using WS 2 /Pt electrocatalysts.…”
Section: Anodic Fuels and Chemicals From Seawater Electrolysismentioning
confidence: 99%
“…Based on experimental data and theoretical simulations, it was shown that the selectivity of the product can be tuned by controlling the proton–electron transfer reaction network. Recently, our group and co-workers 232 reported a novel oxidative reaction for the green electro-synthesis of DAAzF while simultaneously promoting hydrogen production. This emerging green electro-synthesis process can significantly reduce the environmental hazards caused by traditional industrial methods used to synthesize the DAAzF, and the assembled electrolyzer required only a low cell voltage of 1.55 V to reach 100 mA cm −2 using WS 2 /Pt electrocatalysts.…”
Section: Anodic Fuels and Chemicals From Seawater Electrolysismentioning
confidence: 99%
“…For example, Ma et al proposed replacing the OER with green electrosynthesis of ZT and 3,3′-diamino-4,4′-azofurazan (DAAzF), respectively. This solves the slow four-electron transfer kinetics of OER, producing hydrogen with lower energy consumption (Figure b). , …”
Section: Introductionmentioning
confidence: 96%
“…This solves the slow four-electron transfer kinetics of OER, producing hydrogen with lower energy consumption (Figure 1b). 12,13 Given that electrochemical organic synthesis involves electrocatalysis and organic chemistry, the complexity of the reaction leads to the absence of research on the mechanism of the electrosynthesis of EMs. In order to promote the application of electrochemicals in the synthesis of energetic materials, it is necessary to explore the mechanism of electrocatalytic energetic materials at a deeper level and design efficient electrocatalysts.…”
Section: ■ Introductionmentioning
confidence: 99%